Learner Autonomy of Science Using 5E Learning Cycle: Otonomi Pembelajar Sains Menggunakan Siklus Pembelajaran 5E - Fauzi, Fatchul; Mustadi, Ali (Pedagogia : Jurnal Pendidikan, 2019)
This aims to determine the effect of the 5E learning on student learning Autonomy. The research subjects are 84 PGSD students. 5E Learning applicants with the syntax of Engagement, Exploration, Exploration, Elaboration, and Evaluation were carried out in advanced science courses in the second semester. Research with the type of quasi experiment using questionnaires as a measure of student learning Autonomy. The results showed that the mean score of the control group and the experimental group had increased. The Mann-Whitney U test obtained a significance of 0.039 and the effect of the 5E learning showed a high category with score of N gain is 0.98. it can be concluded that the 5E learning affects student learner autonomy.